Processing and preservation: cutting the waste - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Processing and preservation of tropical and subtropical foods J. Maud Kordylas, 414 pp, 1990 price UKL12.00 Available from CTA